Analisis Pengaruh Kualitas Pelayanan dan Ketepatan Pengiriman terhadap Kepuasan Pelanggan JNE Keputih - Panji Aditya Ramadhani Delfipo; Nurani Hartatik (Jurnal Sains dan Teknologi (JSIT), 2026)
With the increasing competition in the courier service industry, companies are required to provide superior service quality and consistent delivery timeliness to achieve customer satisfaction. This study aims to analyze the effect of service quality and delivery timeliness on customer satisfaction at JNE Keputih, Surabaya. A quantitative approach was employed, with data collected through questionnaires distributed to 100 respondents selected using a purposive sampling technique based on predetermined research criteria. The collected data were analyzed using multiple linear regression with the assistance of SPSS software, including validity, reliability, classical assumption, partial (t-test), simultaneous (F-test), and coefficient of determination analyses. The results indicate that all research instruments met the validity and reliability requirements. Service quality has a positive and significant effect on customer satisfaction, with a t-value of 4.053 and a significance value of 0.000. Delivery timeliness also has a positive and significant effect on customer satisfaction, with a t-value of 3.775 and a significance value of 0.000. Furthermore, both variables simultaneously have a significant effect on customer satisfaction, as indicated by an F-value of 259.985 and an Adjusted R² value of 0.843. These findings suggest that improving service quality and maintaining consistent delivery timeliness are strategic factors for JNE Keputih in sustaining customer satisfaction while strengthening its competitiveness in the courier service industry.